Effects of Jugular Vein Occlusion on Cardiovascular Parameters in Horses During Exercise on a Treadmill - Dias, Deborah Penteado Martins; da Silva, Marco Augusto Giannoccaro; Albernaz, Raquel Mincarelli; Gomide, Lina Maria Wehrle; Martins, Carla Braga; Bernardi, Nara Saraiva; Barbosa, José Carlos; Queiroz Neto, Antonio de; de Lacerda Neto, José Corrêa (Elsevier, 2013)
The purpose of the present investigation was to examine the effects of unilateral and bilateral jugular vein occlusion by temporary surgical ligature on the heart rate and arterial and venous blood pressure in sedentary horses during progressive treadmill exercise. Six horses performed three exercise tests (ET). ET1, considered the control, was performed in horses without jugular occlusions. ET2 and ET3 were performed with unilateral and bilateral occlusion by temporary surgical ligature of the jugular veins, respectively. Heart rate, arterial pressure, and pressure of the occluded jugular vein were evaluated. Clinically, the horses presented apathy, head edema, congested mucous membranes, increased capillary refill time, and dysphagia. These signs were observed with the unilateral jugular vein occlusion and became more evident with the bilateral occlusion. Comparing ETs, no differences were observed in heart rate. However, jugular occlusions promoted a decrease in the mean arterial pressure and a severe increase in jugular pressure. Head edema caused by the jugular vein occlusion in the horses could interfere with the autonomic cardiovascular regulation of arterial blood pressure during exercise, likely leading to an impairment of tissue perfusion. Jugular occlusion, even unilateral, also causes severe head venous congestion, leading to venous hypertension that was aggravated by exercise, which could risk development of cerebral edema and neurological damage. The present results obtained from sedentary horses are preliminary data that lead us to suggest that sport horses presenting jugular occlusive thrombophlebitis, even unilateral, may be prevented from performing athletic activities. © 2013 Elsevier Inc. All rights reserved.
Keywords: Equine; Exercise; Hemodynamic; Thrombophlebitis; Treadmill